Now you see me? Auto-ethnographic insights from inside the black box of business incubation. (28th March 2022) - Gupta, Sonali
Abstract : Business incubators are a favourite policy tool used by governments worldwide to stimulate and support entrepreneurship. However, little is known about the challenges in operationalizing an incubator. Scholars have highlighted the lack of access to reliable incubator data, the politically charged environments in which incubators operate and the tendency of incubator management and policymakers to provide positive self-evaluation results to demonstrate the success of such publicly funded initiatives. This paper offers auto-ethnographic insights into operating a business incubator in India. By verbalizing tacit knowledge acquired through personal experiences and elaborating the trials and tribulations of running an incubator, the paper sheds light on an incubator's structural properties, functions and operational dilemmas. It shifts the conversation away from the notion of the incubator as a well-defined entity – having a prescribed model and path to success as defined by its sponsors – toward an organization that needs to experiment, learn from its mistakes and change course, much like the startups it claims to support. To maintain anonymity, pseudonyms are used for the incubator and all the people referred to in the paper.